The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1590/fst.35422
|View full text |Cite
|
Sign up to set email alerts
|

Extraction, physiological function and application of soluble dietary fiber from edible fungi: a review

Abstract: The methods AOAC (Association of Official Analytical Chemists) (Tobaruela et al., 2018) 991.43 is a traditional DF analysis method, mainly analyzing insoluble and soluble higher molecular weight dietary fiber (HMWDF), while methods AOAC 2011.25 is a new dietary fiber analysis method. This method can not only analyze the content of TDF, but also the content of IDF, SDF and resistant starch (RS) (Tobaruela et al.,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 58 publications
0
4
0
Order By: Relevance
“…The water-soluble dietary fibers play an important role at the protection against obesity and diseases [138]. Edible mushrooms are a valuable source of soluble and insoluble dietary fiber [139]. The most important dietary fibers from the mushroom may include (1→3)-β-D-glucan, chitin, mannan [46], xylan, and galactan [140].…”
Section: Pleurotus Ostreatus and Gut Microbiotamentioning
confidence: 99%
“…The water-soluble dietary fibers play an important role at the protection against obesity and diseases [138]. Edible mushrooms are a valuable source of soluble and insoluble dietary fiber [139]. The most important dietary fibers from the mushroom may include (1→3)-β-D-glucan, chitin, mannan [46], xylan, and galactan [140].…”
Section: Pleurotus Ostreatus and Gut Microbiotamentioning
confidence: 99%
“…Dietary fibers are the indigestible and more solid contents of vegetables and fruits, such as peel, membrane, stem, and seed. In the literature, it was reported that dietary fibers play a role in the regulation of the excretory system and the prevention of many diseases such as various types of cancer, cardiovascular diseases, obesity, and gastrointestinal diseases (Ozgoren et al, 2019;Zheng et al, 2022).…”
Section: Chemical Properties Of Gluten-free Muffin Cakesmentioning
confidence: 99%
“…The HPLC method was utilized for the determination of ergosterol content in both the pileus and stipe, as described by Jasinghe and Perera (25). The final sample was injected into HPLC system (Agilent 1290) with a C18 column (YMC Pack ODS-AM-303, 4.6 mm × 250 mm, 5 μm; Agilent Technologies, Wilmington, DE, United States).…”
Section: Determination Of Ergosterolmentioning
confidence: 99%